Preparation and optimization of polyaniline /titanium dioxide /carboxymethyl cellulose powder for effective nickel adsorption - Lee, Michelle Li-Yen; Ishak Ahmad,; Phang, Sook-Wai (Penerbit Universiti Kebangsaan Malaysia, 2024)
Hexanoic acid-doped polyaniline (PAni) is a great potential candidate to replace conventional adsorbent towards the removal of heavy metal waste from electroplating industry, especially nickel (Ni). In this study, different weight % (wt %) of titanium dioxide (TiO2 ) and carboxymethyl cellulose (CMC) are added to form PAni composites with enhanced Ni removal efficiency. All the synthesized samples were examined with FTIR, UV-Vis, conductivity measurement, XRD, TGA, and FESEM to confirm their chemical structures, oxidation states, electrical conductivity, crystallinity and incorporation of metal oxide, thermal stability, and surface morphology, respectively. Among the different samples, PAni / TiO2 20 % exhibited the highest Ni removal efficiency of 37.5 %. Upon further addition of CMC, PAni / TiO2 / CMC 5 % showed the highest Ni removal efficiency of 89.08 %. Optimization of the experimental parameters were conducted and a maximum Ni removal efficiency of 97.88 % was achieved at pH 10, 30 min contact time at a temperature of 30 °C, and with an adsorbent dosage of 0.01 g. This study shows that the composite of PAni / TiO2 / CMC 5 % shows good potential to be applied as adsorbent of the removal of Ni ions.